Perkawinan Campuran Di Bukit Lawang: Praktik, Tantangan, Dan Implikasi Hukum - Rizky, Febby (Institut Syekh Abdul Halim Hasan Binjai, 2024)
Mixed marriages involving Indonesian citizens (WNI) and foreign nationals (WNA) have unique legal implications in Indonesia, particularly governed by Law No. 1 of 1974 on Marriage. This article aims to analyze the compliance of mixed marriage practices in Bukit Lawang with applicable legal provisions, as well as to explore the legal, social, and cultural challenges faced by mixed marriage couples. Based on interviews and field observations, it was found that although mixed marriage couples adhere to existing legal procedures, bureaucratic challenges and cultural differences remain frequent issues.